Philosophy in a time of lost spirit : essays on contemporary theory - Beiner, Ronald, 1953- (University of Toronto Press, 1997)
In this collection of his essays and reviews, Ronald Beiner probes the boundaries of our social world and develops his own intellectual challenge to liberalism in a critical review of contemporary thinkers.